Hexago applying gamification to task management to create a more engaging and efficient workflow in order to preempt delays and improve overall performance of individuals and groups in organizations - Areopagita, Kamille Anne U.
Work related stress has found an increase within both the global workforce among Filipino workers, leading to various physical and psychological issues that impact value and quality of work, and subsequently, organizations. Task and project management programs and methods also tend to be complex and daunting, making it hard to monitor tasks and track progress, not conducive to communication among members, and consequently leading to delays, costs and stress. Research conducted among various employers form different fields and ages showed that deadlines and volume of work are the top causes of stress among employees, while recognition and progress are considered major motivators for work, productivity, and quality. The physical, interpersonal, and intrapersonal work environment also play an important role in forming and engaging workplace, which contributes to employee satisfaction, motivation, productivity, communication, and overall performance. This thesis looks into "gamification" - the utilization of game elements, mechanics, and principles to non-game contexts-as a method of addressing issues of motivation, recognition, workloads, and deadlines in terms of task and project management. The proposed solution is a gamified program that blends roleplaying game (RPG) elements with task management, focusing on instant visual feedback of progress and status of tasks and projects, as well as an engaging format that encourages communication, interaction, recognition, and both cooperation and competition. The product targets employees working in organizations focused on computer-based work, as well as smaller organizations such as startups and university/college organizations. The multi-platform program is designed to give ease of use, tracking, and monitoring of tasks for efficiency in task completion, as well as a more engaging format of task management in order to preempt delays and improve overall performance of individuals and groups in organizations.